Episodic dyscontrol syndrome. Issue 10 (1st June 2010) - McTague, Amy; Appleton, Richard
Abstract : Episodic dyscontrol syndrome (EDS) or intermittent explosive disorder (IED) is a clearly identified category in the Diagnostic and Statistical Manual of Mental Disorders ( DSM IV ). It affects children and adults. Children are often considered to have epilepsy or a mental health problem. The episodes comprise of recurrent attacks of uncontrollable rage, usually after minimal provocation, and may last up to an hour. Following an episode, children are frequently exhausted, may sleep and will usually have no recall. These features often raise the possibility of epilepsy, and children may be referred for an electroencephalogram (EEG). An abnormal EEG may subsequently lead to a diagnosis of epilepsy and the prescription of an anticonvulsant. Five patients with EDS are described, all referred to a single neurology clinic with a possible diagnosis of epilepsy, one of whom was being treated with an anticonvulsant. Four had an EEG, which was normal in two patients and showed "abnormalities" in two, leading to an incorrect diagnosis of temporal lobe epilepsy in one patient. All five children responded to psychological (behavioural) intervention. Recognition of the clinical features of IED/EDS should preclude the need for EEG and other investigations in these patients and prompt referral to psychological services.